Relationship of entrepreneurial orientation and innovation performance of SMEs using PLS-SEM. (15th March 2022) - Iqbal, Shuja; Tian, Hongyun; Qalati, Sikandar Ali; Akhtar, Shamim; Kayani, Arqam Javed
Small and medium-sized enterprises (SMEs) are engines of growth for developing economies. Every SME desires to enhance the business and retain a prominent position in the market. The entrepreneurial orientation plays a critical role in enhancing the innovation performance of SMEs. This study explores the critical role of entrepreneurial orientation and its characteristics concerning the optimised organisational commitment and innovation performance of SMEs in developing economies. This study collected data from 177 employees of SMEs and analysed it using partial least square structured equation modelling in Smart PLS software. The study's findings revealed that risk-taking, innovativeness, motivation, proactiveness, aggressive competition, and autonomy enhance the firms' organisational commitment and innovation performance. Moreover, the findings revealed a decisive mediating role of organisational commitment between the relationship of entrepreneurial orientation and innovation performance. This study helps SMEs' managers develop strategies to enhance their firms' abilities with their employees' increased commitment by valuing their innovative ideas and achieving higher innovation performance.